(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper, we formulate the hypothesis that the cult to the indigenous god Coso/Cossue in the south of the conventus Asturum, evidenced by the discovery of seven votiv altars in the region of The Bierzo (León), was consequence of migrations of groups of worshippers to the god from the Galician coastal regions toward the auriferous exploitations of the Asturian area. To establish the hypothesis, we analyze the other cases of cult diffusion caused by emigrations toward mining areas in the Iberian Peninsula.